2019
DOI: 10.1136/vr.105000
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic factors which predict low private rabies vaccination coverage in dogs in Blantyre, Malawi

Abstract: Although rabies kills approximately 60,000 people globally every year, vaccination of over 70 per cent of the canine population has been shown to eliminate the disease in both dogs and human beings. In some rabies endemic countries, owners are able to vaccinate their dogs through private veterinary clinics. However, uptake of dog vaccinations through private veterinary clinics is often low in many rabies endemic countries. In this study, the authors examined the sociodemographic factors which predicted low pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
8
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 22 publications
2
8
1
Order By: Relevance
“…From these observations, Fissenebert has concluded that the majority of roaming dogs in Arusha are actually owned. This is similar to the situation observed in Blantyre 10 …”
supporting
confidence: 90%
See 4 more Smart Citations
“…From these observations, Fissenebert has concluded that the majority of roaming dogs in Arusha are actually owned. This is similar to the situation observed in Blantyre 10 …”
supporting
confidence: 90%
“…[6][7][8][9] A study by Mazeri and colleagues, summarised on p 281 of this issue of Vet Record, investigated the sociodemographic factors that predict low private rabies vaccination coverage in dogs in Blantyre, Malawi. 10 Of the dogs recorded in this study, 99 per cent were owned, but only 3 per cent had been vaccinated independently at a private clinic. The study found that poverty, high housing density and the dog being male, a puppy, pregnant or lactating were negative predictors for private vaccination.…”
mentioning
confidence: 78%
See 3 more Smart Citations